Effect of different training methods on stride parameters in speed maintenance phase of 100-m sprint running - Cetin, E.; Hindistan, I. E.; Ozkaya, Y. G. (The Journal of Strength and Conditioning Research, 2018)
This study examined the effects of 2 different training methods relevant to sloping surface on stride parameters in speed maintenance phase of 100-m sprint running. Twenty recreationally active students were assigned into one of 3 groups: combined training (Com), horizontal training (H), and control (C) group. Com group performed uphill and downhill training on a sloping surface with an angle of 4°, whereas H group trained on a horizontal surface, 3 days a week for 8 weeks. Speed maintenance and deceleration phases were divided into distances with 10-m intervals, and running time (t), running velocity (RV), step frequency (SF), and step length (SL) were measured at preexercise, and postexercise period. After 8 weeks of training program, t was shortened by 3.97% in Com group, and 2.37% in H group. Running velocity also increased for totally 100 m of running distance by 4.13 and 2.35% in Com, and H groups, respectively. At the speed maintenance phase, although t and maximal RV (RVmax) found to be statistically unaltered during overall phase, t was found to be decreased, and RVmax was preceded by 10 m in distance in both training groups. Step length was increased at 60-70 m, and SF was decreased at 70-80 m in H group. Step length was increased with concomitant decrease in SF at 80-90 m in Com group. Both training groups maintained the RVmax with a great percentage at the speed maintenance phase. In conclusion, although both training methods resulted in an increase in running time and RV, Com training method was more prominently effective method in improving RV, and this improvement was originated from the positive changes in SL during the speed maintaining phase.